2001
DOI: 10.1126/science.1061967
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Size and Temperature on Metabolic Rate

Abstract: We derive a general model, based on principles of biochemical kinetics and allometry, that characterizes the effects of temperature and body mass on metabolic rate. The model fits metabolic rates of microbes, ectotherms, endotherms (including those in hibernation), and plants in temperatures ranging from 0 degrees to 40 degrees C. Mass- and temperature-compensated resting metabolic rates of all organisms are similar: The lowest (for unicellular organisms and plants) is separated from the highest (for endotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

184
3,396
25
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 3,192 publications
(3,707 citation statements)
references
References 10 publications
184
3,396
25
15
Order By: Relevance
“…The gradient relating MLSP to mass was the same as that derived previously using a smaller data set (Lindstedt and Calder 1976). In a recent re-emergence of allometric scaling investigations, West et al (1997) and Gillooly et al (2001) suggested that most energetics relationships conform to allometric exponents of around 0.75, as determined by the rate at which resources are delivered to cells via fractal network systems. However, this proposition has been questioned on both theoretical Konarzewski 2004, 2005;Clarke 2006) and empirical grounds (Glazier 2005), and our data similarly did not support 0.75 allometric scaling.…”
Section: Discussionsupporting
confidence: 67%
“…The gradient relating MLSP to mass was the same as that derived previously using a smaller data set (Lindstedt and Calder 1976). In a recent re-emergence of allometric scaling investigations, West et al (1997) and Gillooly et al (2001) suggested that most energetics relationships conform to allometric exponents of around 0.75, as determined by the rate at which resources are delivered to cells via fractal network systems. However, this proposition has been questioned on both theoretical Konarzewski 2004, 2005;Clarke 2006) and empirical grounds (Glazier 2005), and our data similarly did not support 0.75 allometric scaling.…”
Section: Discussionsupporting
confidence: 67%
“…The temperature-dependence of growth rates in different species has gained much attention in the context of the metabolic theory of ecology (Gillooly et al, 2001;Brown et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…where P 0 is a normalization constant that varies between taxa and environments, β is the mass scaling exponent, E is an activation energy that gives the temperature dependence, k is Boltzmann's constant; and T is temperature in kelvin (17,27,28). Average residence time of carbon molecules within an individual is obtained by substituting Eq.…”
Section: Significancementioning
confidence: 99%